EFEKTIVITAS STRATEGI PEMBELAJARAN PROBLEM SOLVING PADA KALANGAN MAHASISWA PAK - Harapan Agustina Zebua; Eni Rombe; Fianus Tandiongan (JOURNAL of THEOLOGICAL STUDENTS, 2023)
This study aims to determine how big and how effective is the implementation of problem solving learning strategies among PAK students at the Alfa Omega Christ Theology College Semarang. In this study, researchers used a combination research method (mixed methods).The results of the study on the Effectiveness of Problem Solving Learning Strategies Among PAK Students at the Alfa Omega Christ Theology College Semarang with the results of the previous hypothesis that 60% was rejected because it was proven that the quantitative and qualitative data analysis was 84% so that it was greater than the previous hypothesis in the very good category, in meaning that PAK lecturers and PAK students have tried to apply problem solving learning strategies well. According to the findings, researchers still find obstacles experienced by lecturers and students in implementing problem solving learning strategies, namely in problem solving steps with research results.